Spatially resolved spectroscopy across stellar surfaces: III. photospheric Fe I lines across HD189733A (K1 V) - Dravins, Dainis; Gustavsson, Martin G. H.; Ludwig, Hans-Günter (Arxiv, 2018)
Spectroscopy across spatially resolved stellar surfaces reveals spectral line profiles free from rotational broadening, whose gradual changes from disk center toward the stellar limb reflect an atmospheric fine structure that is possible to model by 3-D hydrodynamics. Previous studies of photospheric spectral lines across stellar disks exist for the Sun and HD209458 (G0 V) and are now extended to the planet-hosting HD189733A to sample a cooler K-type star and explore the future potential of the method. During exoplanet transit, stellar surface portions successively become hidden and differential spectroscopy between various transit phases uncovers spectra of small surface segments temporarily hidden behind the planet. In Paper I, observable signatures were predicted quantitatively from hydrodynamic simulations. From observations of HD189733A with the ESO HARPS spectrometer at R=115,000, profiles for stronger and weaker Fe I lines are retrieved at several center-to-limb positions, reaching adequate S/N after averaging over numerous similar lines. Retrieved line profile widths and depths are compared to synthetic ones from models with parameters bracketing those of the target star and are found to be consistent with 3-D simulations. Center-to-limb changes strongly depend on the surface granulation structure and much greater line-width variation is predicted in hotter F-type stars with vigorous granulation than in cooler K-types. Such parameters, obtained from fits to full line profiles, are realistic to retrieve for brighter planet-hosting stars, while their hydrodynamic modeling offers previously unexplored diagnostics for stellar atmospheric fine structure and 3-D line formation. Precise modeling may be required in searches for Earth-analog exoplanets around K-type stars, whose more tranquil surface granulation and lower ensuing microvariability may enable such detections.
Gesehen am 30.01.2019